United Republic of Tanzania : Selected Issues-Macrofinancial Issues. (IMF Staff Country Reports; Country Report ;, 2016)
This Selected Issues paper analyzes the financial sector in Tanzania. The Tanzanian financial system has a number of characteristics commonly seen in other low-income countries. The system is relatively small, dominated by banks, and has not been particularly inclusive. Costs related to basic financial services have come down. However, in other areas, progress remains limited. Firms' access to credit remains a problem, access to the financial infrastructure continues to lag, and market development remains at a low level. The banking system overall is well-capitalized and reasonably profitable, but there is considerable variation among bank categories.